Arah Kebijakan dan Strategi Pendidikan Islam Kementerian Agama Indonesia - Zamahsari Abdul Aziz (Edu Journal Innovation in Learning and Education, 2024)
The educational path is a vehicle through which students develop their potential in an educational process by the objectives of education. In reality, there are still many problems in implementing the education system, especially Islamic education in Indonesia. The transformation of Islamic education, which refers to the direction of the Ministry of Religion's policy in the field of education, needs to be carried out by further developing a broader concept of education by the dynamics and developments of society. The method used in this study is library research. The results of this study indicate that: 1) Islamic education must be directed to (i) creating Islamic morals, faithful, and pious humans, (ii) believing it as a truth, and (iii) proving it in action. 2) The direction of Islamic education policy in the Ministry of Religious Affairs of the Republic of Indonesia includes: a) Strengthening the education system with a moderate perspective, b) Increasing the quality of educators in educational units, c) Increasing student participation in educational units, d) Increasing the number of teachers who meet the SNP, e) Increasing the standard of education quality, f) Strengthening student character education, g) Increasing the quality of vocational education based on cooperation with the world of work/industry, h) Increasing the quality of PTKI with an international reputation, i) Increasing the quality of PTK graduates accepted in the world of work, j) Increasing the quality of research utilization, k) Increasing the effective and accountable organizational governance of the Directorate General of Islamic Education.